Implementasi Chatbot NgirimWA guna Optimalisasi Respons Pelanggan dan Peningkatan Kualitas Layanan Pelanggan pada UMKM Pakaian Bayi - Fandevi Maitri; Claresta Antonia; Julius Sutrisno (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The rapid growth of the digital ecosystem encourages SMEs to improve customer service quality through digital communication platforms such as WhatsApp Business. However, the limited automation features available on WhatsApp Business still require customer service activities to be handled manually, especially during peak operational hours. This study aims to analyze the implementation of a knowledge-based chatbot using the NgirimWA platform to improve operational efficiency in the TISUKA baby clothing SME. The research applies a qualitative approach through observation, interviews, and literature studies. In addition, Value, Rare, Inimitable, Organization (VRIO), Strengths, Weaknesses, Opportunities, Threats (SWOT), Business Model Canvas (BMC), and Segmentation, Targeting, Positioning (STP) analyses were conducted to understand the business’s internal and external conditions before chatbot implementation. The findings indicate that the use of the NgirimWA chatbot accelerates customer communication, reduces repetitive manual responses, and improves the consistency of product information delivered to customers. The chatbot also helps business owners reduce operational workload, which previously required approximately 3–5 hours daily to respond to customer inquiries manually. Furthermore, chatbot implementation contributes to better customer service quality by providing faster, more informative, and continuously available responses outside operational hours. This study demonstrates that NgirimWA can serve as a relevant digital solution for SMEs to improve customer service efficiency and support business digital transformation.